Analysis Of Differences in Financial Performance Before And After The Covid-19 Pandemic (At PT. Garuda Indonesia Tbk. 2018-2021 Period) - Devinta Aulia Febriana; Wuryaningsih Dwi Lestari (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2023)
The Large-Scale Social Restrictions policy has a huge impact on all sectors, not only the health sector but also the economic sector. The government is very concerned about the Indonesian economy because there has been an economic decline and slowdown. The existence of the Covid-19 pandemic has made many companies experience a decline in profits. This research uses a type of quantitative research, where data is expressed with numbers and the results of calculations and measurements. In this study, researchers will take data samples on the PT Garuda Indonesia Tbk website (https://www.garuda-indonesia.com) for the period 2018-2021, this type of research is time series data or only once collected based on time sequence. The results of this study are that the measurement of profitability ratios with ROA can be found that there are no differences in financial performance before and after the Covid-19 pandemic. Based on the results of measuring the liquidity ratio with CR, it can be seen that there is no difference in financial performance before and after the Covid-19 pandemic. Based on the results of measuring the solvency ratio with DER, it can be seen that there are no differences in financial performance before and after the Covid-19 pandemic.